Penerapan Metode Problem Solving Berbantuan Classroom Dalam Meningkatan Prestasi Belajar Mahasiswa PGSD - I Ketut Ngurah Ardiawan (Edukasi: Jurnal Pendidikan Dasar, 2021)
The purpose of this study was to describe the increase in student achievement through class-assisted problem solving methods and to describe student responses related to the application of class-assisted problem solving methods. This research is a classroom action with the research subjects of all third semester students of the Primary School Teacher Education study program at STAH Negeri Mpu Kuturan Singaraja, totaling 34 students. The object of research is student achievement in Elementary School Indonesian Language Subject. The method of analysis in this research is descriptive qualitative. The results of this study are as follows: 1) there is an increase in student achievement from 66% in cycle I to 80% in cycle II, or an increase of 14% is in the good category and 2) the proportion of the average student response to the learning process is 78 , 5% are in the good category.Keywords: Problem Solving, Classroom, Learning Achievement